REVITALIZATION DEAL IN AKAD HYBRIDS IN SHARIA BANKING VALUE BASED ISLAMIC JUSTICE - Masduqi Masduqi; Gunarto Gunarto; Akhmad Khisni (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Judging from the background of its formation, the formulation of the hybrid contract is motivated by a passion to expand the range of Shariah banking in order to be more competitive than conventional financial institutions. The world's conventional financial institutions have advanced so rapidly, because it is centuries old. The products offered is already so varied. Banking Shari'ah established with a mission of Islam in economics to be applied in the financial institutions are required to be able to race competitively catch up to conventional financial institutions. The spirit of this competition can sometimes only shift the original ideals of the Shari'ah banking so out of the idealistic mission. Ideally, Shari'ah banking mission to operationalize by function with fairness, honesty and mission enliven real sector. Akad which became the main base is musharakah or mudarabah with the principle of sharing in a partnership approach. However, because of the demands of profitability and encouraged the spirit of acceleration enlarge market share, concerns the question that arises is whether the main concern of Shariah banking can be shifted from the spirit of the mission to realize the ideal into the spirit of competition in the formalities of the subordinated kesyari'ahan ideal mission?  Looking at the above, there were some fundamental problems with the implementation of the contract, namely whether the hybrid will not shift the original ideals of Shariah banking, because there is concern shifted to the usury that no longer different from the conventional financial institutions. A further problem of how to revitalize the agreement in the contract hybrids in value based banking Shari'ah Islamic justice. This problem appears motivated by a sense of concern author of various hybrid forms of contract that can not represent the substance of justice is a principle addressed in the rules of jurisprudence muamalah. Thus this dissertation research is expected to create more hybrid contract represents an agreement.